KONSUMSI BERAS ORGANIK PADA TINGKAT RUMAH TANGGA DI KOTA YOGYAKARTA - Pradesi Sulistyana; Jangkung Handoyo Mulyo; Jamhari Jamhari (Agro Ekonomi, 2014)
This research was conducted (1) to determine the organic rice consumption patterns in the region of Yogyakarta City (2) to determine the characteristics of organic rice consumed in the region of Yogyakarta City and (3) to identify the factors influencing the demand for organic rice in Yogyakarta City. The basic method for this research is descriptive analysis. The research located in Yogyakarta City were determined through incidental sampling, there were 35 organic rice consumers as respondents. The data was analyzed by multiple linier regression analysis by Ordinary Least Square (OLS). The result showed that (1) there are 3 categories for the consumption patterns of organic rice at the household level in Yogyakarta City, they are  routinely, mixed, and occasionally, with the following results: total food expenditure per month 2,1 million rupiahs - 5 million rupiahs (45,71%), the amount of consumption per month is 21-40 kg by the number of family 5-7 members (51,43%), most consumers choose distributor as a place to purchase organic rice (60%), the main reason of organic rice consumption is the health factor (88,57%), consumers are satisfied to consume organic rice (85,71%), the long of consumption is 1-6 months (42,86%), source of information about the benefits of organic rice from the electronic media (36,36%) and information about the characteristics of organic rice from distributors, (2) consumers of organic rice at the household in Yogyakarta City (40%) consume organic rice from menthik wangi variety that has typical characteristic of white color, rice color level is clear, the rice smells fragrant, rough texture, low broken rice percentage (10-20%), sweet taste, rice fluffiness level is fluffier and more durable resistance, (3) the consumption of organic rice is positively affected by organic rice consumption are the price of non-organic rice, instant noodles price, health factor and negatively affected by price of tempe and tahu price. Non-organic rice and instant noodles are substitutes for organic rice, while tempe and tahu are complements of organic rice.